Mentors’ Perceptions of Factors Associated with Change in Early Childhood Classrooms - Howe, Nina; Jacobs, Ellen (Alberta Journal of Educational Research, 2014)
Mentors’ perceptions of factors associated with educational change were identified following an individualized mentoring program about constructivist curriculum for early childhood educators. A qualitative case study analysis of the mentors’ journals of six classrooms was conducted to review their perceptions of change. Classroom environment quality was assessed with the Early Childhood Environmental Rating Scale-Revised (ECERS-R) before and after the intervention program. At post-intervention, mentors reported that classrooms with increased ECERS-R Activities scores were likely to engage in behaviors promoting change, for example reflective skills, documenting children’s learning, and challenging their own beliefs. In contrast, educators in classrooms with relatively stable post-intervention ECERS-R Activities scores appeared to create barriers that inhibited change. For example, they were less willing to challenge their beliefs, make changes in practice, and to document children’s learning. Recommendations presented in the paper focus on successful implementation of mentoring programs; policy implications indicate that individualized mentoring programs require proper financial and personnel supports. Suite à un programme de mentorat individualisé portant sur un curriculum constructiviste pour les éducateurs de la petite enfance, nous avons recueilli les perceptions des mentors quant aux facteurs associés aux changements éducatifs. Nous avons entrepris une analyse qualitative de cas basée sur les journaux des mentors qui évoquaient six salles de classe et ce, afin d’étudier la perception qu’ils avaient du changement. La qualité du milieu scolaire a été évaluée avec l'Échelle d'évaluation de l'environnement préscolaire révisée (ÉÉEP-R) avant et après le programme d’intervention. Après l’intervention, les mentors ont signalé que les salles de classe ayant augmenté leur score selon l’échelle ÉÉEP-R étaient plus aptes à adopter des activités promouvant le changement, par exemple, celles impliquant les habiletés de réflexion, la documentation des apprentissages par les enfants et la remise en question des croyances. Toutefois, les enseignants des salles de classe dont le score selon l’échelle ÉÉEP-R après l’intervention était demeuré relativement stable semblaient créer des obstacles qui freinaient les changements. Par exemple, ils étaient moins disposés à remettre en question leurs croyances, d’apporter des modifications à leur pratique et de documenter l’apprentissage des élèves. Les recommandations proposées portent sur la mise en œuvre réussie de programmes de mentorat; parmi les implications stratégiques, notons la nécessité d’un appui financier adéquat et d’un soutien approprié de la part du personnel.